PENDIDIKAN ISLAM PADA MASA NABI MUHAMMAD SAW DAN KHULAFAUR RASYIDIN: KONTRUKSI SOSIAL - Azizah Aryati; Mindani; Yusmita Rahmatika; Aisyh Anggun Putri; Sansan Gempur Pahsya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze how Islamic education shaped social construction during the time of the Prophet Muhammad and the Caliphs. This study uses a library research method and data analysis was conducted using the theory of Huberman and Miles, which consists of data reduction, data presentation, and drawing conclusions. The results of the study indicate that Islamic education is a social construction formed through ongoing social, cultural, and spiritual interactions, which then shape social reality. The process of forming this social reality occurs through interaction and dialectics with three main stages from Berger and Luckman’s theory, namely externalization, objectivation, and internalization. Thus, Islamic education during the time of the Prophet Muhammad and the Caliphs was not only a process of knowledge transfer, but also a transformative force that succeeded in creating and institutionalizing a new social order, values, and norms in society.